ACTIVITY OF DEVELOPMENT CENTERS IN THE EDUCATIONAL ACTIVITY OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - Abduxakimova Maxfuza Abduraxmonova (Academia Science Repository, 2023)
This article talks about ways to improve the system of preschool education, the content of implementing innovative pedagogical technologies in the process of preschool education, and the use of methods of implementing innovative pedagogical technologies in the process of preschool education.